2023
DOI: 10.20944/preprints202301.0345.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of the Peruvian Andean Legume, tarwi (Lupinus mutabilis), With High Quality SNPs

Abstract: Lupinus mutabilis Sweet (Fabaceae), “tarwi” or “chocho”, is an important grain legume in the Andean region. In Peru, studies on tarwi have been mainly focused on morphological features, however, the have not been molecularly characterized. Currently, it is possible to explore genetic parameters of plants with reliable and modern methods like genotyping-by-sequencing (GBS). We here for the first time used single nucleotide polymorphisms (SNPs) markers to infer the genetic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Catalán et al 77 reported a high level of variability using eight microsatellites in 83 accessions of six races of maize from Cusco. The genetic diversity of the nine races and one subrace of maize assessed in this study is very high, which is concordant with its improvement status (i.e., landraces), as reported for other landraces of beans 78 , peas 79 , squash 80 , tarwi 30 , or wheat 81 , among others. Our genetic diversity indices align with other studies on maize landraces.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Catalán et al 77 reported a high level of variability using eight microsatellites in 83 accessions of six races of maize from Cusco. The genetic diversity of the nine races and one subrace of maize assessed in this study is very high, which is concordant with its improvement status (i.e., landraces), as reported for other landraces of beans 78 , peas 79 , squash 80 , tarwi 30 , or wheat 81 , among others. Our genetic diversity indices align with other studies on maize landraces.…”
Section: Discussionsupporting
confidence: 89%
“…Thereafter, we employed the TASSEL v5.2.42 bioinformatic pipeline 27,28 for SNPs calling with maize Zm-B73-REFERENCE-NAM-5.0 29 as the reference genome. Parameters employed in this pipeline were the same as in the study of Huaringa et al 30 . Data curation was performed using software VCFtools v0.1.16 31 with the following criteria of retention: (i) minimum minor allele frequency of 0.1, (ii) number of alleles less than or equal to 2, and (iv) maximum missing data of 0.1.…”
Section: Genotyping-by-sequencingmentioning
confidence: 99%